Studi Metode penyaringan ketahanan kedelai terhadap kekeringan meng gunakan larutan polyethylen glycol=A Study on Screening Method for Drought Resistance of Soybean Using Polyethylen Glycol - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1997)
ABSTRACT A two-stage experiment devised to study the screening method for drought resistance of soybean using polyethylen glycol (PEG) was set up in the Laboratory of Seed Science and Technology and in the Experimental Field of Departement of Agronomy, Faculty of Agriculture, Gadjah Mada University from April up to September 1996. The experiment, involving two factors, was arranged in Completely Randomized Design with three replications. In either stage of the experiment, osmotic potential of PEG, ranging from 0 bar as control check, up to -0,75 bar with -0,25 interval, was the first factor_ The second factor was soybean genotype. In the first stage, twenty five genotypes were used, which were then reduced into five genotypes in the second stage experiment for further evaluation for their drought resistance, ranging from resistant to susceptible. Experimental results indicated that osmotic potential of PEG significantly affected all soybean characteristics under consideration, but flowering time. Different soybean genotypes differed in their characters, and responded differently to PEG as indicated from significant effect of the interaction, except for imbibition at day 1 and 2 in the first stage experiment, and plant height at 30, 45, and 60 dap in the second stage experiment. In the first stage experiment, different soybean genotypes differed in their resistance toward PEG induced drought based on seed germination percentage, seedling root length, and vigor index. Dieng variety showed high value for those three characters, indicating that Dieng was resistant. Moderate resistant reaction was shown by Singgalang variety Kipas Putih showed an intermediate, Galunggung showed a moderate susceptible, while Wills was susceptible. Comparison of mean of genotypes evaluated in the second stage experiment was done for plant height at 60 dap, fresh and dry weight of both plant and roots, root-shoot ratio, relative growth rate at 45 dap, and at harvest, flower number, pod number, seed yield per plant, and stress index. Under osmotical potential leading to a drought stress, characteristics of resistant genotypeitad a higher value than those of genotype of lower degree of resistance. The reduction was in parallel with the degree of resistance. Correlation analysis of germination characters and adult stage plant characters revealed a significant ascneiation particularly under high osmotic potential (-0,50 bar).